Addressing viral hepatitis in the opiate substitution setting: An integrated nursing model of care. (March 2015) - Fragomeli, Vince; Weltman, Martin
Abstract: Despite the availability of effective therapies for hepatitis C virus (HCV) and B virus (HBV), only a minority of infected patients receive treatment. In the general population, morbidity and mortality associated with chronic HCV is now successfully being addressed through the use of antiviral therapy. In Australia, an estimated 41% to 68% of people who inject drugs (PWID) are HCV positive, and between 28% and 59% of users are estimated to have been exposed to HBV. Although current treatment guidelines suggest that active drug use should not preclude people from HCV treatment, uptake of therapy thus far has been low. Patient, physician, social, and logistical‐related barriers contribute to the low uptake of HCV treatment among PWID. Traditional means of managing HCV infection—referral to secondary or tertiary health centers—historically has a poor track record in increasing therapy uptake among this population. The same is true for people with chronic HBV who inject drugs. Close to 50 000 Australians receive opioid substitution therapy (OST) through a range of services, including public and private clinics, thus this setting is an ideal target for identifying and treating people at risk for and already infected with HBV and HCV. Over the last 11 years, a nursing model of care initiated by a teaching hospital in Sydney, Australia that integrates viral hepatitis screening, assessment, and treatment into the OST setting has enhanced access to services among the marginalized injecting drug use population.